ANALISIS FAKTOR KEPATUHAN PASIEN TB PARU DALAM MINUM OBAT - Sitorus, Jenti (Ensiklopedia of Journal, 2024)
A preliminary survey conducted by researchers at the HKBP Balige General Hospital HKBP Balige General Hospital, it is known that there are 136 patients with Tb. But in However, in the implementation of treatment, only 57% routinely take Tb treatment. In In general, one of the causes of failure to cure patients with pulmonary TB is non-compliance with treatment. patient in treatment. The purpose of the study was to determine the compliance factors patients in taking medication. This type of research uses quantitative with a cross sectional approach. Research conducted in August 2023. The research sample amounted to 46 people. Results The results showed that there was a relationship between family support with a p value of 0.016 on treatment compliance. Tb. It is recommended that patients with pulmonary TB be willing to undergo treatment according to the doctor's recommendations, adhere to treatment, listen to and obey the rules and directions of the doctor. doctor's advice, obedient to treatment, willing to listen and obey the rules and directions of health workers and PMOs, always telling if there are complaints. health workers and PMO, always tell if there are complaints or side effects side effects of the drugs taken.    Keywords: Family Support, Adherence, Tuberculosis